2013
DOI: 10.1016/j.immuni.2013.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial TNF Receptor 2 Induces IRF1 Transcription Factor-Dependent Interferon-β Autocrine Signaling to Promote Monocyte Recruitment

Abstract: SUMMARY Endothelial-dependent mechanisms of mononuclear cell influx are not well understood. We showed that acute stimulation of murine microvascular endothelial cells expressing the receptors TNFR1 and TNFR2 with the soluble cytokine TNF, led to CXCR3 chemokine generation. The TNF receptors signaled through Interferon regulatory factor-1 (IRF1) to induce interferon-β (IFN-β) and subsequent autocrine signaling via the type I IFN receptor and the transcription factor STAT1. Both TNFR2 and TNFR1 were required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
131
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(141 citation statements)
references
References 49 publications
8
131
1
1
Order By: Relevance
“…*P < 0.05; **P < 0.001;***P < 0.0001. a view, work has shown that IFNAR1-deficient mice are resistant to TNF-α-induced shock in vivo (27). Consistent with our observations, this pathway of TNF-α-induced IFN-β expression has been demonstrated to occur through an IRF-1-dependent mechanism (38) and appears to occur within endothelial cells as well as macrophages (39). Underlining the importance of IFNAR1, we also have observed that LPS-or polyI:C-induced necroptosis of macrophages is unaffected by the lack of TNFR1/2 but is highly dependent on IFNAR1 expression.…”
Section: Discussionsupporting
confidence: 91%
“…*P < 0.05; **P < 0.001;***P < 0.0001. a view, work has shown that IFNAR1-deficient mice are resistant to TNF-α-induced shock in vivo (27). Consistent with our observations, this pathway of TNF-α-induced IFN-β expression has been demonstrated to occur through an IRF-1-dependent mechanism (38) and appears to occur within endothelial cells as well as macrophages (39). Underlining the importance of IFNAR1, we also have observed that LPS-or polyI:C-induced necroptosis of macrophages is unaffected by the lack of TNFR1/2 but is highly dependent on IFNAR1 expression.…”
Section: Discussionsupporting
confidence: 91%
“…A role for endothelial IRF-1 as a regulator of TNF-α-mediated VCAM-1 induction in endothelial cells was reported before [20,21] . Our data reveal that IRF-1 is expressed in mouse renal endothelial and tubular epithelial cells, and that LPS can induce renal IRF-1 expression in vivo.…”
Section: Discussionmentioning
confidence: 86%
“…In endothelial cells, IRF-1 was recently shown to regulate TNF-α-mediated signaling, which specifically regulated the expression of the adhesion molecule VCAM-1 [20,21] . Recently, we also showed that RIG-I can control VCAM-1 expression in response to LPS challenge [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, IRF1 is required for TNF induction of IFN-b to promote monocyte recruitment (13,14). Recently, systematic screening of antiviral effectors identified human IRF1 as one of six broadly acting effectors to defend against all viruses tested in IFN-dependent and IFN-independent manners (15,16), underscoring the physical relevance of IRF1 in the innate antiviral response.…”
mentioning
confidence: 99%